Management of intrathoracic phosphaturic mesenchymal tumor by nonintubated uniportal video‐assisted thoracic surgery in a fragile patient. Issue 5 (5th August 2021) - Ferrari, Michele; Palleschi, Alessandro; Bartoli, Francesca; Polli, Federico; Armiraglio, Elisabetta; Parafioriti, Antonina; Croci, Giorgio A.; Tosi, Davide
Abstract: Background: Phosphaturic mesenchymal tumors are rare neoplasms, frequently presenting with osteomalacia. These neoplasms usually grow at a slow rate and are associated with unspecific symptoms. Case: In this study, we present the case of a 70‐year‐old woman who had been suffering from musculoskeletal pain, hypophosphatemia, and spontaneous fractures. Positron emission tomography with Gallium showed increase uptake in a subpleural lesion. Conclusion: The patient underwent surgical excision of the subpleural lesion with a non‐intubated uniportal video‐assisted thoracoscopic surgery approach.